2012
DOI: 10.3892/ol.2012.763
|View full text |Cite
|
Sign up to set email alerts
|

The promoter methylation of the Syk gene in nasopharyngeal carcinoma cell lines

Abstract: Abstract. The aim of this study was to investigate the mRNA and protein expression levels of the Syk gene as well as its promoter methylation in nasopharyngeal carcinoma (NPC) cell lines. The CNE-1 (highly differentiated), CNE-2 (poorly differentiated) and NP69 (non-cancerous human immortalized nasopharyngeal epithelial cells) cell lines were used in the present study. The MS-PCR, Q-RT-PCR and western blotting methods were used to examine the Syk gene promoter methylation levels and mRNA and protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hypermethylation of the SYK gene promoter was demonstrated to be associated with a loss of SYK gene expression in a variety of malignant cancers, including breast cancer ( 21 ), gastric cancer, nasopharyngeal carcinoma ( 22 ) and hepatocellular cancer ( 23 ). In CRC, the present authors previously demonstrated that global SYK methylation was an independent prognostic factor for overall survival ( 12 ), but the expression and biological functions of alternative splicing SYK isoforms in CRC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation of the SYK gene promoter was demonstrated to be associated with a loss of SYK gene expression in a variety of malignant cancers, including breast cancer ( 21 ), gastric cancer, nasopharyngeal carcinoma ( 22 ) and hepatocellular cancer ( 23 ). In CRC, the present authors previously demonstrated that global SYK methylation was an independent prognostic factor for overall survival ( 12 ), but the expression and biological functions of alternative splicing SYK isoforms in CRC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hypermethylation of the SYK promoter region, which may lead to complete silencing of the gene or to a decrease in its [3,9,17,18]. As of yet, it has remained unknown whether polymorphisms within the SYK gene promoter region may affect its transcription and/or may be associated with the risk to develop CRC.…”
Section: Discussionmentioning
confidence: 99%